Association between Soluble ST2 Basal and Global Longitudinal Strain 2D-Speckle on Tracking Echocardiography with Left Ventricle Remodeling after an Acute Myocardial Infarction - Fani Suslina Hasbuan1, Muhammad Aminudin1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Left ventricle remodeling (LVR) is an important prognosis post acute myocardial infarction (AMI). Soluble ST2 is a novel biomarker for myocardial fibrosis and left ventricular remodeling. Global Longitudinal Strain (GLS) which is a reflection of the longitudinal layer of cardiac muscle can be detected in the early ischemia phase, and has been proven to predict the occurrence of left ventricular remodeling post AMI. Objective: To identify the association between soluble ST2 basal and GLS with LVR post AMI. Method: This research was conducted from August to December 2015. This is an analytic observational study with one group pretest and post test design. Soluble ST2 and GLS examinations were performed twice (2-5 days after AMI and 12 weeks after therapy). The results were analyzed using Spearman’s correlation test. Result: The sample size was 45 respondents (82.2% males, average age of 55.47 ± 10.13 years, 84.4% STEMI). There was a strong correlation between high ST2 basal levels with LVR (p = 0.0001 r = +0.723) and ?ST2 with LVR (p = 0.0001 r = 0.639). The association of low GLS with LVR was p = 0.015 and r = + 0.362. Conclusion: A significant LVR was found post-AMI, the high soluble ST2 basal and low GLS basal may be a factor for predicting LVR.